Click dimers to target HIV TAR RNA conformation - Kumar, Sunil (2012)
A series of neomycin dimers have been synthesized using “Click chemistry” with varying functionality and length in the linker region to target the HIV-1 TAR RNA region of HIV virus. TAR (Transactivation Response) RNA region, a 59 base pair stem loop structure located at 5′-end of all nascent viral transcripts interacts with its target, a key regulatory protein, Tat, and necessitates the replication of HIV-1 virus. Neomycin, an aminosugar, has been shown to exhibit multiple binding sites on TAR RNA. This observation prompted us to design and synthesize a library of triazole linked neomycin dimers using click chemistry. The binding between neomycin dimers and TAR RNA was characterized using spectroscopic techniques including FID (Fluorescent Intercalator displacement), FRET (fluorescence resonance energy transfer) competitive assay, circular dichroism (CD) and UV-thermal denaturation. UV thermal denaturation studies demonstrate that neomycin dimers binding increase the melting temperature (T(m)) of the HIV TAR RNA up to 10 °C. (Ethidium bromide) displacement (FID) and FRET competition assay revealed nanomolar binding affinity between neomycin dimers and HIV TAR RNA while in case of neomycin, only a weak binding was detected. More importantly, most of the dimers showed lower IC(50)s towards HIV TAR RNA, when compared to the fluorescent Tat peptide and show increased selectivity over mutant TAR RNA. Cytopathic effects investigated using MT-2 cells indicate a number of the dimers with high affinity towards TAR show promising anti HIV activity.